2023
DOI: 10.1002/ajoc.202300077
|View full text |Cite
|
Sign up to set email alerts
|

Photoredox synthesis of Vicinal Dichloride using FeCl3 as chlorine source

Abstract: This work presents a photo‐redox vicinal dichlorination of acrylamides using a naturally abundant chlorine source (FeCl3). The LMCT of FeCl3 is responsible for the chlorine radical inducement, while the tetra‐n‐butylammonium decatungstate (TBADT) catalytic system enhanced the process. This method exhibits extraordinarily mild conditions, not requiring external ligands and low E factors, which enables scalable synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Combined with the pioneering works in literatures and our experiments above, [8–12] we proposed the possible photocatalytic mechanism mediated by FeCl 3 (Scheme 3). A possible pathway reported by Duan group etc involves light‐induced LMCT in FeCl 3 , [10,13a,17] which could promote the formation of free Cl ⋅ (route i).…”
Section: Resultsmentioning
confidence: 62%
See 3 more Smart Citations
“…Combined with the pioneering works in literatures and our experiments above, [8–12] we proposed the possible photocatalytic mechanism mediated by FeCl 3 (Scheme 3). A possible pathway reported by Duan group etc involves light‐induced LMCT in FeCl 3 , [10,13a,17] which could promote the formation of free Cl ⋅ (route i).…”
Section: Resultsmentioning
confidence: 62%
“…A series of alkylethylenes were also tested as the substrates (Table 2, entries 11-19). As shown in Table 2 (entry 11), dichlorination of allylbenzene and 4-methoxyallylbenzene gave the target products in as high as 93 % and 91 % yields, respectively (Table 2,entries 11,12). Nallylphthalimides and butenyl benzoates were also smoothly coverted to the target products in 73-88 % yields.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…29,30 We identified catalysts FeCl 3 and FeBr 3 due to their inexpensiveness, low level of toxicity, and ability to perform direct hydrogen atom transfer (HAT) under visible light. 31–33 After some initial optimization (see ESI†), we observed that PIBVE degradation in acetone at short reaction times (Fig. 1a, entries 1 & 2) was more efficient in the presence of FeBr 3 —in terms of number average molecular weight ( M n )—than in the presence of FeCl 3 .…”
Section: Resultsmentioning
confidence: 99%